Prostate Cancer Screening in Jamaica: Results of the Largest National Screening Clinic. (29th February 2016) - Morrison, Belinda F.; Aiken, William; Mayhew, Richard; Gordon, Yulit; Reid, Marvin
Abstract : Prostate cancer is highly prevalent in Jamaica and is the leading cause of cancer-related deaths. Our aim was to evaluate the patterns of screening in the largest organized screening clinic in Jamaica at the Jamaica Cancer Society. A retrospective analysis of all men presenting for screening at the Jamaica Cancer Society from 1995 to 2005 was done. All patients had digital rectal examinations (DRE) and prostate specific antigen (PSA) tests done. Results of prostate biopsies were noted. 1117 men of mean age 59.9 ± 8.2 years presented for screening. The median documented PSA was 1.6 ng/mL (maximum of 5170 ng/mL). Most patients presented for only 1 screen. There was a gradual reduction in the mean age of presentation for screening over the period. Prostate biopsies were requested on 11% of screening visits; however, only 59% of these were done. 5.6% of all persons screened were found to have cancer. Of the cancers diagnosed, Gleason 6 adenocarcinoma was the commonest grade and median PSA was 8.9 ng/mL (range 1.5–1059 ng/mL). Older men tend to screen for prostate cancer in Jamaica. However, compliance with regular maintenance visits and requests for confirmatory biopsies are poor. Screening needs intervention in the Jamaican population.